A Proposed Conceptual Framework for Enhancing the Role of Training in Human Resource Development in the Kingdom of Saudi Arabia - Ismail, Sarah Mohammed; Al-Hafzi, Shahad Abdul Khaliq; Ali, Baderiya Mohammad; Mohammed, Badr Saleh Al-Abdi (The Arab Journal of Administration, 2024)
This study aimed to present a proposed conceptual framework for enhancing the role of training in human resource development in the Kingdom of Saudi Arabia. To achieve this objective, a descriptive methodology was employed. The study encompassed a general framework that included an introduction, problem statement, research questions, significance, study terminology, previous studies, and their utilization. It also comprised three dimensions: The first dimension presented the conceptual framework of training and qualification, which encompassed its concept, objectives, importance, types, and fundamental considerations to be taken into account. The second dimension presented the conceptual framework of human resource development, covering the concept of human development, the concept of human resource development, objectives of human resource development, functions of human resource development, and strategic models for human resource management. The third dimension discussed the proposed framework, including its objectives, justifications, components, and implementation requirements. The study results indicated that the role of training in human resource development in the Kingdom of Saudi Arabia could be enhanced through the activation of the strategic approach to training and qualification, as well as the implementation stages of training and qualification, which included preparation, execution, and the utilization of knowledge management practices in HR management and development. Additionally, the localization of training and qualification within organizations should be activated.